Mental health and economic concerns from March to May during the COVID-19 pandemic in Canada: Insights from an analysis of repeated cross-sectional surveys. (December 2020) - Zajacova, Anna; Jehn, Anthony; Stackhouse, Matthew; Choi, Kate H.; Denice, Patrick; Haan, Michael; Ramos, Howard
Abstract: Background: The COVID-19 pandemic impacted the psychological wellbeing of populations worldwide. In this study, we assess changes in mental health during the early months of the pandemic in Canada and examine its relationship with another prominent problem during this time, economic concerns. Methods: Analyses were based on two cycles of the nationally representative repeated cross-sectional Canadian Perspectives Survey Series (N=4627 in March and 4600 in May). We described the changes in mental health and economic concerns between March and May, and assessed the relationship between the two characteristics. Results: Mental health declined significantly during the early months of the COVID-19 pandemic: the proportion of Canadian adults who reported only good/fair/poor mental health grew from 46% to 52% from March to May. Economic concerns including food insecurity were an important correlate of 'bad' mental health, as was younger age, female gender, and Canada-born status. Contrary to expectations, however, economic concerns lessened during this time frame. Conclusions: These findings suggest that policies to mitigate economic stress, such as Canada's Emergency Response Benefit, may have eased mental health deterioration in early pandemic months through a reduction in financial hardship. Interventions to increase the economic security of the population will have far-reaching consequences in terms of improved mental health, and should be continued throughout the pandemic. Highlights: The disruptions and restrictions of the COVID-19 pandemic have had a powerful effect on mental health, as well as economic concerns, in populations worldwide. We found that mental health deteriorated during early stages of the COVID-19 pandemic from March to May 2020 among Canadian adults. However, economic concerns lessened during this time, contrary to expectations. This improvement, which coincided with the government's economic interventions, reduced the decline of mental health.